10-Year Impact of Transcatheter Aortic Valve Replacement Leaflet Design (Intra- Versus Supra-Annular) in Mortality and Hemodynamic Performance - Scotti, Andrea; Fovino, Luca Nai; Coisne, Augustin; Fabris, Tommaso; Cardaioli, Francesco; Massussi, Mauro; Rodinò, Giulio; Barolo, Alberto; Boiago, Mauro; Continisio, Saverio; Montonati, Carolina; Sciarretta, Tommaso; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background The impact of transcatheter aortic valve replacement (TAVR) leaflet design on long-term device performance is still unknown. This study sought to compare the clinical and hemodynamic outcomes of intra- (IA) versus supra-annular (SA) TAVR designs up-to 10-years following implantation. Methods Consecutive patients with at least 5-years follow-up following TAVR for severe symptomatic aortic stenosis from June 2007 to December 2016 were included. Bioprosthetic valve failure (BVF) and hemodynamic valve deterioration (HVD) were defined according to VARC-3 updated definitions and estimated using cumulative incidence function to account for the competing risk of death. Results A total of 604 patients (82 years; 53% female) were analyzed and divided into IA (482) and SA (122) groups. Overall survival rates at 10-years were similar (IA 15%, 95%CI: 10–22; SA 11%, 95%CI: 6–20; p = 0.21). Compared to the SA TAVR, mean transaortic gradients were significantly higher and increased over time in the IA group. IA TAVRs showed higher 10-year cumulative incidences of BVF (IA 8% vs. SA 1%, p = 0.02) and severe HVD (IA 5% vs. SA 1%, p = 0.05). The occurrence of BVF and HVD in the IA group occurred primarily in the smallest TAVR devices (20–23-mm). After excluding these sizes, the cumulative incidences of BVF (IA 5% vs. SA 1%, p = 0.40) and severe HVD (IA 2% vs. SA 1%, p = 0.11) were similar. Conclusion In this study, TAVR leaflet design had no impact on survival at 10-years. IA devices showed higher transaortic gradients and cumulative incidences of HVD and BVF predominantly occurring in the smallest valve sizes.